2013
DOI: 10.1021/am404129u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processable High Dielectric Constant Nanocomposites Based on ZrO2 Nanoparticles for Flexible Organic Transistors

Abstract: A solution-based strategy for fabrication of high dielectric constant (κ) nanocomposites for flexible organic field effect transistors (OFETs) has been developed. The nanocomposite was composed of a high-κ polymer, cyanoethyl pullulan (CYELP), and a high-κ nanoparticle, zirconium dioxide (ZrO2). Organic field effect transistors (OFETs) based on neat CYELP exhibited anomalous behavior during device operation, such as large hysteresis and variable threshold voltages, which yielded inconsistent devices and poor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…Reports on applications of inorganic nanoparticles in OFETs are sparse in the literature and have been limited mainly to their use as nanocomposites in gate dielectric layers. [29][30][31] Zinc oxide nanoparticles have been used in polyfluorene composites for lightemitting field effect transistors, 32 whilst Q-ZnO has been applied as a component in a hybrid OFET bilayer device fabricated with P3HT as the organic film. 33 Blends of P3HT and CdSe have been studied in OFETs 34 and also in organic photovoltaics devices.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on applications of inorganic nanoparticles in OFETs are sparse in the literature and have been limited mainly to their use as nanocomposites in gate dielectric layers. [29][30][31] Zinc oxide nanoparticles have been used in polyfluorene composites for lightemitting field effect transistors, 32 whilst Q-ZnO has been applied as a component in a hybrid OFET bilayer device fabricated with P3HT as the organic film. 33 Blends of P3HT and CdSe have been studied in OFETs 34 and also in organic photovoltaics devices.…”
Section: Resultsmentioning
confidence: 99%
“…[75][76][77][78] For example, a pentacene-based organic field-effect transistor with a crosslinked cyanoethyl pullulan dielectric layer was found to operate under a low gate voltage of − 3 V with a remarkably high mobility of~8.62 cm 2 V − 1 s − 1 , an on/off current ratio of~10 5 , and a steep sub-threshold slope of 0.099 V per dec. 75 Furthermore, Beaulieu and co-workers added ZrO 2 nanoparticles to neat cyanoethyl pullulan as physical crosslinks to eliminate the charge-trapping effect and improve the stability and performance of the P3HT transistor devices. 77 In addition to functionalized pullulan, Petritz et al 78 demonstrated the use of trimethylsilyl cellulose as an organic/inorganic bilayer gate dielectric for organic field-effect transistors and complementary inverters, as shown in Figure 13. Using this bilayer dielectric, the fabricated pentacene-and C 60 Charge-trapping electrets in organic field-effect transistor memory As mentioned, using modified cellulose as the dielectric layer in transistor devices results in a different device performance because the concentration of the induced charge carrier at the dielectric/ semiconductor interface is very different from traditional dielectrics.…”
Section: Gate Dielectric Layers In Organic Field-effect Transistorsmentioning
confidence: 99%
“…Moreover for low power operations in TFT it is meaningful to maintain the dielectric thickness as thin as possible . To this aim, nanodielectrics such as nanoparticles or self‐assembled monolayers or multilayers have been recently developed and implemented in OFETs . Another class of material, the supported lipid layers, with thicknesses of a few nanometers also constitutes good candidates.…”
Section: Introductionmentioning
confidence: 99%